Policy Implementation to Accelerate Stunting Reduction in Cilengkrang Village, Bandung Regency - Ananda, Marsha Radhia; Dina (Social Impact Journal, 2025)
This research analyzes the implementation of stunting reduction acceleration policy in Cilengkrang Village, Bandung Regency, using Edward III's theory of communication, resources, disposition, bureaucratic structure. A qualitative approach was applied, with data from the Village Head, KPM, Village Midwife, Community Facilitator, parents of stunted children, and pregnant women. The results showed significant progress in stunting prevention efforts in this village. Communication is well implemented through various channels such as Posyandu, stunting meetings, WhatsApp groups, classes for pregnant women and toddlers, and door-to-door visits. In terms of resources, both human (KPM, midwives, health workers) and material (village fund allocation, provincial assistance, equalization funds, and KPM operations), have been optimally utilized. Disposition shows high commitment from the village head and stakeholders. They actively lead and monitor the program, and are proactive in mentoring and data reporting. This commitment has rubbed off on the community, encouraging them to pay more attention to child and infant nutrition. However, the bureaucratic structure needs improvement. KPM tends to report only midwife data; inaccuracies in this data can lead to misidentification of cases. Intensive coordination between KPM and midwives is needed. Overall, Cilengkrang Village has shown strong dedication in tackling stunting. This success is driven by effective communication, optimal resources, and positive disposition. To achieve Zero Stunting, strengthening coordination and data accuracy in the bureaucratic structure is crucial.